The impact of NiPc additive and laser light dielectric properties of E63 nematic liquid crystal - Kilic, Mehmet; Ozdemir, Zeynep Guven; Canli, Nimet Yilmaz; Bulgurcuoglu, Ayse Evrim; Koysal, Oguz; Yilmaz, Omer; Okutan, Mustafa (TAYLOR & FRANCIS LTD, 2016)
In this work, the electrical properties of the pure nematic liquid crystal (E63) and different concentrations Nickel Phthalocyanine (NiPc) doped (E63+1% NiPc, E63+3% NiPc and E63+5% NiPc) E63 have been investigated by means of dielectric spectroscopy measurements under laser light illumination. The variations of the real (epsilon') and imaginary (epsilon) parts of dielectric constant with frequency have been studied. According to e0 versus voltage graphics, threshold voltage, Vth has been calculated. It has been observed that while NiPc doping increases the Vth, the application of laser light has a remarkable decreasing effect on threshold voltage, Vth. The absorption coefficients, a, and relaxation times, tau, have also been calculated for determining the relaxation mechanism. It has been revealed that the relaxation type of these materials is nearly-Debye type regardless of the laser illumination. Moreover, the dielectric strength has been analysed both Debye and Cole-Cole models. Furthermore, conductivity mechanisms of these composites under dark and laser illumination have been investigated for four frequency regions. It has been shown that conductivity mechanism of the composites are not affected by application of laser light above omega = 6x10(4) rad/s.
Keywords: Dielectric properties; conductivity mechanism; laser light illumination; Debye model; Cole-Cole model; FREQUENCY-DEPENDENT CONDUCTIVITY; PHTHALOCYANINE; Materials Science; Physics